A comparative analysis of the antimicrobial efficacy of different concentrations of silver nanoparticles and chlorhexidine against Enterococcus faecalis - In vitro study - Pooja Warade; Manoj Likhitkar; Anant Kumar Heda; Deepali Birla; Thanima Chandran; Neha Ingle (Wolters Kluwer Medknow Publications, 2024)
Introduction: Root canal irrigants combat endodontic microbial flora, effectively targeting resilient microbes like Enterococcus faecalis, which persist despite treatment. Chlorhexidine (CHX), as an irrigant, boasts broad-spectrum antibacterial activity, notable substantivity in dentine, and favorable biocompatibility. In the realm of nanotechnology, the use of silver nanoparticle (AgNP) solutions appears promising, given their strong antibacterial and antimicrobial properties. Objective: The objective of the study was to compare the antimicrobial effectiveness of varying concentrations (1%, 0.75%, and 0.5%) of AgNPs and 2% CHX against E. faecalis. Materials and Methods: Four irrigant solutions, including 1%, 0.75%, and 0.5% AgNPs and 2% CHX with gentamicin as the control, will be assessed. The ATCC 29212 strain of E. faecalis will be cultivated at 37°C on brain-heart infusion Broth plates. After 48 h, the bacterial population will be quantified by counting colony-forming units on agar plates. Each irrigant will be applied to the plates, and the resulting bacterial inhibition zone will be measured. Results: Our study demonstrates the antimicrobial effects of 1%, 0.75%, and 0.5% AgNPs and 2% CHX against E. faecalis. While 2% CHX exhibited superior activity, AgNPs at various concentrations also displayed inhibitory effects against E. faecalis. Conclusion: In conclusion, this study highlights the antimicrobial properties of 1%, 0.75%, and 0.5% AgNPs and 2% CHX against E. faecalis. The results indicate that 2% CHX exhibits superior activity, while AgNPs at various concentrations also demonstrate inhibitory zones against E. faecalis.